The Effect of Slow Deep Breathing Exercises on Elderly Women With Hypertension - Widarti, Rini; Hermawati; Wahyuni, Endah Sri (P3M Universitas 'Aisyiyah Surakarta, 2024)
Background: The elderly or the elderly are the last stage of the human life cycle and experience degenerative processes in various aspects, especially in older women, which results in a higher risk of exposure to disease and ends in death, one of which is hypertension. Older women are closely related to the occurrence of hypertension when a woman experiences menopause. Treatment of hypertension can be done using non-pharmacological methods using slow deep breathing exercises. Purpose: To determine the effect of slow deep breathing exercises on older women with hypertension. Method: This study used the time series quasi-experimental method with one pre-test and post-test group. Results: The analysis of the Paired Sample T Test yielded p-values of 0.049 and 0.009 (p < 0.05), indicating that the alternative hypothesis (Ha) is supported. This implies that there is a significant impact of slow deep breathing exercises on blood pressure in older women when comparing the measurements before and after the intervention. Conclusion: Slow deep breathing exercises have an impact on the blood pressure of older women with hypertension.